2012
DOI: 10.1002/adma.201201687
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering of Monolayers and Nanopatterns

Abstract: In a molecularly decorated surface, the molecular tiles are “glued” to the surface by binding constants and possibly further “glued” to each other by cooperativity factors. At odds with mosaics, these “glues” come with the tiles and cannot be removed or supplemented. Binding polynomials quantify glue amounts from experimental data and may predict molecular self-organization on surfaces that can be exploited in organic (opto-)electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The current demand of increasingly smaller devices urges to explore new methods capable of producing ordered nanostructured surfaces, aimed not only at future applications but also at the study of new properties arising from these systems at the atomic level. Among the different strategies to generate nanostructured surfaces, the bottom-up approach, which exploits the capability of the systems to self-assemble and self-organize, is the primary tool supporting recent advances in nanotechnology. In this context, organic molecules are not simply the building blocks of a supported architecture, but they can effectively pattern the morphology of a metal surface through the structural rearrangement associated with their preferential surface adsorption position, eventually yielding mesoscopic templates. One of the most suitable family of molecules for nanoarchitectures are tetrapyrrole molecules (porphyrins and phthalocyanines among others), which are highly relevant components for the design of novel nanodevices, especially for photovoltaic applications. …”
mentioning
confidence: 99%
“…The current demand of increasingly smaller devices urges to explore new methods capable of producing ordered nanostructured surfaces, aimed not only at future applications but also at the study of new properties arising from these systems at the atomic level. Among the different strategies to generate nanostructured surfaces, the bottom-up approach, which exploits the capability of the systems to self-assemble and self-organize, is the primary tool supporting recent advances in nanotechnology. In this context, organic molecules are not simply the building blocks of a supported architecture, but they can effectively pattern the morphology of a metal surface through the structural rearrangement associated with their preferential surface adsorption position, eventually yielding mesoscopic templates. One of the most suitable family of molecules for nanoarchitectures are tetrapyrrole molecules (porphyrins and phthalocyanines among others), which are highly relevant components for the design of novel nanodevices, especially for photovoltaic applications. …”
mentioning
confidence: 99%
“…One approach to tackling this complexity at a fundamental level is by examining the various contributions to the free energy of self-assembly, using statistical approaches. 15,[48][49][50] Distinct formalisms have been developed for supramolecular and block copolymer bulk self-assembly, 15 as well as surface-bound molecules. 50 Thermodynamic and kinetic aspects of the process have been examined in an approximative or qualitative fashion, including the role of entropy, 15,51 polymorphism, 51 pair interactions 50 and cooperativity.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly, which embodies different components to form various packing arrangements in a permissive environment and is considered to be a promising supplement to nanofabrication, has historically come from studying supramolecular systems. During the self-assembly, individual components interactions via noncovalent forces such as van der Waals (vdWs) interactions, hydrogen bonds, π–π stacking, electrostatic, metal–organic coordination, and dipole–dipole intermolecular forces are always present as competing forces to dominate the supramolecular order. Among a variety of organic functional groups, alkane or alkyl is one of most important building units to control the self-assembly structures. The adsorption of assembled alkanes, which is considered essential to the stabilization and epitaxial growth, is closely related to the intermolecular interactions through two-dimensional (2D) crystallization, in addition to the adsorbate–substrate interactions. , This important effect of stabilization of organized assemblies by alkyl substituents has been used as an effective approach to anchor functional molecules on surfaces. Dipole–dipole interaction is another ubiquitously existed noncovalent interaction in 2D supramolecular self-assemblies as long as polar chemical groups are incorporated into the molecules. It has been reported that the interfacial dipole moment created by charge-transfer between Schiff base group and the substrate can significantly modulate the self-assembly patterns . Zimmt and co-workers described the critical role of ether oxygen atoms and {CF 2 /CF 2 } dipolar interactions exert in driving the morphology and patterning of the anthracene moiety on surfaces. Although some useful knowledge has been gained by theoretical simulation, the understanding of dipole–dipole interactions in 2D self-assemblies is generally limited, especially as compared to that about hydrogen bonding, for example.…”
Section: Introductionmentioning
confidence: 99%